Can Kinesiotaping Reduce Pain in Rib Fractures?: A Randomized Prospective Study - Dal, İsmail; Bektaş, Özgür; Kader, Sibel; Bodur, Gözde (Informa UK Limited, 2024)
The aim of this study is to investigate the effect of kinesiotaping on pain scores in patients with rib fractures following isolated thoracic trauma.In this randomized prospective study, patients with isolated thoracic trauma and rib fractures were randomized into kinesiotaping and control groups between January 24, 2024, and October 1, 2024. Patients in the control group received standard analgesic treatment. In the kinesiotaping group, kinesiotaping bands were applied in addition to the standard treatment. Pain scores using the visual analog scale (VAS) were recorded at admission, the 24th hour, the 4th day, and the 7th day, and the results were statistically compared.A total of 118 patients were evaluated. Eighty-four patients did not meet the inclusion criteria. The 34 patients included in the study were randomized into kinesiotaping and control groups. The two groups were demographically homogeneous. On the 4th day, the mean VAS score was significantly lower in the kinesiotaping group (2.7 ± 1.2) compared to the control group (4.1 ± 1.9) (p = 0.037). No statistically significant difference in VAS scores was observed on the other days.In patients with rib fractures, pain scores decreased more rapidly in those treated with analgesics plus kinesiotaping compared to those treated with analgesics alone.ClinicalTrials.gov, NCT06222320. Registered on January 15, 2024.
Keywords: Medicine (General); R5-920; rib fracture; Clinical Trial Report; visual analog scale; pain; kinesiotaping.